THE INFLUENCE OF INTERNAL AND EXTERNAL FACTORS ON THE PROFITABILITY OF ISLAMIC COMMERCIAL BANKS IN INDONESIA - Imam Sopingi; Tjiptohadi Sawarjuwono; Imron Mawardi; Kusnul Ciptanila Yuni K. (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
This study aims to investigate the influence of internal and external factors on the Islamic Commercial Banks' Profitability in Indonesia. The internal factors consist of Capital Adequacy Ratio (CAR), Financing to-Deposits (FDR), Non-Performing Loan (NPF), Cost Inefficiency (BOPO), and Net Operating Profit Margin (NPM) meanwhile the external factors consist of Third-Party Deposits (DPK) and Interest rate. Profitability is one of the important factors in the success and continuity of a company's operations. The method used is regression analysis using monthly data from June 2018 to June 2023. The data used include CAR, FDR, NPF, BOPO, NOM, DPK, and ROA from the Financial Services Authority (OJK) meanwhile the interest rate through the Central Bureau of Statistics (BPS) website. The results showed that CAR, FDR, and Interest Rate did not affect profitability. NPF and NOM have a positive effect on profitability meanwhile BOPO and DPK have a negative effect on profitability.